Influence of Barrier Wind Forcing on Heat Delivery Toward the Greenland Ice Sheet. Issue 4 (10th April 2018) - Fraser, Neil J.; Inall, Mark E.
Abstract: A high‐resolution numerical hydrodynamic model of Kangerdlugssuaq Fjord and the adjacent southeast Greenland shelf region was constructed in order to investigate the dynamics of fjord‐shelf exchange. Recent studies have suggested that rapid exchange flows, driven by along‐shelf barrier wind events, are the dominant agent of exchange between fjord and shelf. These events are prone to occur during the winter, when freshwater forcing is minimal and observations of the fjord interior are scarce. Subglacial freshwater discharge was held at zero, so that any buoyancy‐driven overturning circulation was driven by melting alone. The model described a geostrophically balanced background flow transporting water masses between the fjord mouth and the glacier terminus, indicating that rotational effects are of order‐one importance. Barrier wind events were found to trigger coastally trapped internal wave activity within fjord, temporarily enhancing exchange and vertical mixing, and causing warm water to oscillate in the along‐fjord direction. These internal waves were also found to enhance the background flow via Stokes' drift. Heat delivery through the fjord mouth was smaller than that recorded in summer observations, however the system is more effective at delivering this heat to the head of the fjord. There exists the potential for wintertime melting at the ice‐ocean interface to be significant to the same order as summertime melting. Key Points: Winds excite coastal trapped waves which drive intermediary circulation and enhance geostrophic mean flow Heat delivery toward glacier front in winter comparable to that in observed in summer Increased advection and vertical mixing causes enduring changes to conditions in fjord mouth